Analysis of ecosystem resilience in Jiuzhaigou Valley Scenic Area under the effect of geohazards - Sui, Haixia; Liu, Chang; Ye, Chengming; Xu, Xiaolong; Sui, Tianbo (Frontiers in Earth Science, 2023)
The effect of geohazards on the ecological environment and ecological spatial pattern had received wide attention from scholars. But the positive role played by ecological restoration projects in restoring the ecological environment and reducing geohazards influence was usually neglected. The Jiuzhaigou Valley Scenic Area is a world natural heritage, an area with a high incidence of geohazards and a demonstration area for ecological restoration projects. Based on remote sensing technology, this paper adopted InVEST model (Integrated Valuation of Ecosystem Services and Tradeoffs) and ecological landscape index to extract information about spatio-temporal changes in Jiuzhaigou from 2013 to 2020. And this study conducted a quantitative analysis of the ecological recoverability of Jiuzhaigou in the cases of artificial restoration and spontaneous restoration under different types of geohazards. The results showed that forests play a vital role in maintaining and controlling habitat quality; artificial restoration can significantly ameliorate the impact of geohazards on the scenic area. As of 2020, the forest area of the scenic area recovered 3.868 〖km〗^2, and the habitat quality index rebounded to 98.88% of the historical high. The ecological restoration project significantly shortened the time for the scenic area to recover its ecosystem service capability.